Distribution and antimicrobial resistance analysis of gram-negative bacilli isolated from a tertiary hospital in Central China: a 10-year retrospective study from 2012 to 2021 - Shi, Ting; Xie, Liangyi (Frontiers in Microbiology, 2023)
Background: Gram-negative bacilli are one of the most common causes of various infections in clinical. The emergence and global spread of multi-drug resistant gram-negative bacilli has become a major challenge in the global public health field. Method: A total of 51189 non-repetitive strains of gram-negative bacilli were isolated in clinical settings. The antimicrobial susceptibility testing was conducted by using the automated VITEK 2 compact system and the matched AST susceptibility test card, complemented by the disk diffusion method. The antimicrobial susceptibility results were interpreted by CLSI. Rates of MDR and XDR in K. pneumoniae, A. baumannii, P. aeruginosa were investigated. Used the chi-square test to determine whether the antimicrobial resistance rates of four major gram-negative bacilli isolated from ICU and non-ICU department have statistical differences. Results: E. coli (31.4%), Klebsiella spp. (21.2%), Acinetobacter spp. (13.8%), P. aeruginosa (11.0%) were the most frequently isolated gram-negative bacilli. E. coli was the top one organism isolated from urinary tract(68.4%), bloodstream(39.9%), body fluid(33.2%), wound and pus(37%), except for respiratory tract (8.8%). Whereas A. baumannii and K.pneumoniae were the major isolated organisms from respiratory tract. A. baumannii showed high resistance to fluoroquinolones, β-lactam/β-lactamase inhibitor combinations class, ceftazidime, cefepime, imipenem and meropenem, the resistance rates reached more than 70%. Ceftazidime showed a lower resistance rate to E.coli than ceftriaxone. For E.coli, fluoroquinolones showed a high resistance rate (ciprofloxacin 61.36% and levofloxacin 53.97%), whereas amikacin, carbapenems exhibited a lower resistance rate fluctuating at 2%. A. baumannii and K. pneumoniae showed rapid increases in carbapenem resistance whereas E. coli had the lowest resistance rate and remain stable at 2%. A. baumannii exhibited the highest rate of MDR and XDR, reaching 60% -80% and 45% -55%, respectively. Compared to non-ICU departments, the resistance rates of four major gram-negative bacilli in the ICU department were much higher and the differences were statistically significant (P<0.05). Conclusions: Amikacin, carbapenems and piperacillin/tazobactam exhibited relatively high sensitivity, whereas fluoroquinolones showed high resistance rate whether they can be the first-line antimicrobials for empirical treatment of UTI should take more consideration. The gram-negative bacilli in ICU were more resistance than that in non-ICU.